2005
DOI: 10.1097/01.mpa.0000160959.21580.41
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 4 Detected in Exocrine Pancreas and the Change of Expression in Cerulein-induced Pancreatitis

Abstract: TLR4 protein was expressed in pancreas and localized to epithelial (pancreatic duct) or endothelial (vessels) tissues; TLR4 responded favorably to the inflammatory process, and the change of expression was characterized as a rapid up-regulation in the early stage of CIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Representative FACS plots are shown from 3 independent experiments (n ≥ 3 per group). (18). In order to determine the contribution of and CORM-2's effect on hematopoietic TLR4 in AP, we generated chimeric mice by engrafting WT recipients with either WT or TLR4 KO BM cells (WT→WT or TLR4 KO→WT mice, respectively).…”
Section: Corm-2 Ameliorates Established Experimental Apmentioning
confidence: 99%
“…Representative FACS plots are shown from 3 independent experiments (n ≥ 3 per group). (18). In order to determine the contribution of and CORM-2's effect on hematopoietic TLR4 in AP, we generated chimeric mice by engrafting WT recipients with either WT or TLR4 KO BM cells (WT→WT or TLR4 KO→WT mice, respectively).…”
Section: Corm-2 Ameliorates Established Experimental Apmentioning
confidence: 99%
“…A report has indicated that in the early stage of acute pancreatitis, the expression levels of TLR4, TNF-, and IL-6 in pancreas of acute pancreatitis patients are significantly higher than those in the control ones, the level of plasma TNF-in acute pancreatitis patients increases subsequently, and the increase of plasma TNF-level is positively correlated with the expression of TLR4, suggesting that the up-regulation of TLR4 expression on the surface of peripheral blood monocytes in patients with early acute pancreatitis might be associated with the activation of the innate immune system in the early stage of the disease [150]. Results of animal experiments have shown that TLR4 messenger RNA is also up-regulated in the pancreas of rats with cerulein-induced edematous pancreatitis in the early stage, the serum levels of cytokines such as TNF-are subsequently elevated, and the two phenomena are correlated [151].…”
Section: Toll-like Receptor-4 (Tlr4)mentioning
confidence: 76%
“…Immunoreactivity of IL-6 has been detected in acinar, pancreatic islet, and duct cells during human pancreatitis (Jablonowska et al, 2008). Experimental induction of AP leads to elevated expression of toll-like receptor 4 in pancreatic ductal epithelium, vascular endothelium, and islet, further complicating the inflammatory signals (Li et al, 2005). Taken these findings together, an intricate cross talk between pancreatic cells in regulating inflammatory response might exist.…”
Section: Redox-sensitive Erk-induced Pancreatic Inflammation 453mentioning
confidence: 88%